DETERMINAN ASSET STRUCTURE, GROWTH OPPORTUNITY, DAN FIRM SIZE TERHADAP CAPITAL STRUCTURE PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Novianty Novianty (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research was conducted to determine the determinants of asset structure, growth opportunity, firm size and profitability on capital structure in primary consumer goods sector companies on the Indonesia Stock Exchange. The data population in this research is all companies in the primary consumer goods sector on the Indonesia Stock Exchange, totaling 54 companies. The financial report data used in this research is from 2016 to 2020. The company sampling technique is to use the purposive sampling method. The data analysis techniques used are descriptive statistics and multiple linear analysis. The results of this research show that asset structure has a negative and significant effect on capital structure, while growth opportunity and firm size have no effect on capital structure in primary consumer goods sector companies on the Indonesia Stock Exchange.